Satisfaction Assessment of Service Receivers of Daily Rehabilitation Institutions in Tehran Based on the Consumerism Aproach - Farideh Hemmati; Hossein Kakouei; Habib Agha-Bakhshi; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: This research was conducted in line with Consumerism viewpoint and its objective is to assess the satisfaction level of service receivers in 12 daily rehabilitation Institutions of Tehran in order to improve service supply processes based on the service receivers viewpoints, which can ultimately provide suitable backgrounds for incorporating them into the service supply process. Materials & Methods: The sample society consists of 133 people of the service receivers who were selected through ranked random sampling. Because no studies of this field had been made previously, a viewpoint assessing Questionnaire was drawn up on a scale of 5 Likert degrees containing 92 questions and one repeatedly answered question, and its average of satisfaction mark (3.71) and variance deviation (0.297) was determined. Results: By the way after the question lacking correlation had been omitted, the number of question decreased to 68. Analyses made by use of SPSS 7.5 Win and Excel Win software not only presented a high level of satisfaction in many fields, but also distinguished cases of dissatisfaction. Conclusion: The age, sex and level of education were not suggestive and impact on the level of satisfaction. By the way, the service receivers made suggestion on the modification and Improvement of the processes.